Pengaruh Kualitas Pelayanan Melalui Teknologi Informasi Dan Kualitas Produk Terhadap Keputusan Pembelian di CV Pustaka Bengawan - Cipto Utomo, Bangun Prajadi; Santosa, Tri Djoko (Politeknik Indonusa Surakarta, 2023)
This study seeks to assess the impact of both service quality through information technology and product quality on purchasing decisions, examining these influences both individually and collectively. The research was carried out among customers of CV Pustaka Bengawan, employing a quantitative causal analysis to scrutinize the independent variables—product quality and service via information technology—in relation to the dependent variable, namely, purchasing decisions. Data collection involved the distribution of questionnaires to 100 respondents, and subsequent analysis utilized multiple linear regression, t-test, F-test, and coefficient of determination. The findings reveal a positive and statistically significant influence of both product quality and service through information technology on purchasing decisions, both in isolated and combined contexts. The combined contribution of product quality and service via information technology to purchasing decisions is estimated at 63.7%, with the remaining 36.3% being attributable to other variables. Therefore, companies are expected to improve their service quality through information technology to increase purchasing decisions. Additionally, they should improve product quality, especially for products that are already accepted and in demand by consumers. Future researchers can conduct research on purchasing decisions using different approaches and indicators based on different theories.